Inhibition of Nuclear Receptor Coactivator 3 Attenuates Fibrosis in Murine Models of Systemic Sclerosis - Pötter, Sebastian; Dees, Clara; Bergmann, Christina; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (2018)
EVALuna2:34967

NCOA3 AMPLIFIES PROFIBROTIC TRANSCRIPTIONAL PROGRAMS IN SYSTEMIC SCLEROSIS - Dees, Clara; Pötter, Sebastian; Fuchs, Maximilian; Bergmann, Christina; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Soare, A.; Ramming, Andreas; Ceppi, Paolo; Schett, Georg; Kunz, Meik; Distler, H. W. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150

TGF-beta-Induced Epigenetic Silencing of SOCS3 Facilitates STAT3 Signaling to Promote Fibroblast Activation and Tissue Fibrosis in Systemic Sclerosis - Dees, Clara; Zhang, Yun; Pötter, Sebastian; Bergmann, Christina; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (2017)
EVALuna2:33431

TGF-β-induced epigenetic deregulation of SOCS3 facilitates STAT3 signaling to promote fibrosis - Dees, Clara; Pötter, Sebastian; Zhang, Yun; Bergmann, Christina; Zhou, Xiang; Luber, Markus; Wohlfahrt, Thomas; Karouzakis, Emmanuel; Ramming, Andreas; Gelse, Kolja; Yoshimura, Akihiko; Jaenisch, Rudolf; et al. (Journal of Clinical Investigation, 2020)
Fibroblasts are key effector cells in tissue remodeling. They remain persistently activated in fibrotic diseases, resulting in progressive deposition of extracellular matrix. Although fibroblast activation may be initiated by external factors, prolonged activation can induce an “autonomous,” self-maintaining profibrotic phenotype in fibroblasts. Accumulating evidence suggests that epigenetic alterations play a central role in establishing this persistently activated pathologic phenotype of fibroblasts. We demonstrated that in fibrotic skin of patients with systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease, TGF-β induced the expression of DNA methyltransferase 3A (DNMT3A) and DNMT1 in fibroblasts in a SMAD-dependent manner to silence the expression of suppressor of cytokine signaling 3 (SOCS3) by promoter hypermethylation. Downregulation of SOCS3 facilitated activation of STAT3 to promote fibroblast-to-myofibroblast transition, collagen release, and fibrosis in vitro and in vivo. Reestablishment of the epigenetic control of STAT3 signaling by genetic or pharmacological inactivation of DNMT3A reversed the activated phenotype of SSc fibroblasts in tissue culture, inhibited TGF-β-dependent fibroblast activation, and ameliorated experimental fibrosis in murine models. These findings identify a pathway of epigenetic imprinting of fibroblasts in fibrotic disease with translational implications for the development of targeted therapies in fibrotic diseases.
CRIS-Team Scopus Importer:2020-05-12

THE AP1 TRANSCRIPTION FACTOR CJUN AMPLIFIES HEDGEHOG-INDUCED FIBROBLAST ACTIVATION AND TISSUE FIBROSIS - Bergmann, C.; Merlevede, B.; Beyer, Christian; Hallenberger, L.; Brandt, Adrian; Dees, Clara; Pötter, Sebastian; Bozec, Aline; Schett, Georg; Distler, Jörg (2018)
EVALuna2:34992

The histone demethylase Jumonji domain-containing protein 3 (JMJD3) regulates fibroblast activation in systemic sclerosis - Bergmann, Christina; Brandt, Adrian; Merlevede, Benita; Hallenberger, Ludwig; Dees, Clara; Wohlfahrt, Thomas; Pötter, Sebastian; Zhang, Yun; Chen, Chih-Wei; Mallano, Tatjana; Liang, Ruifang; Kagwiria, Rosebeth; et al. (Annals of the Rheumatic Diseases, 2017)
Systemic sclerosis (SSc) fibroblasts remain activated even in the absence of exogenous stimuli. Epigenetic alterations are thought to play a role for this endogenous activation. Trimethylation of histone H3 on lysine 27 (H3K27me3) is regulated by Jumonji domain-containing protein 3 (JMJD3) and ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX) in a therapeutically targetable manner. The aim of this study was to explore H3K27me3 demethylases as potential targets for the treatment of fibrosis.JMJD3 was inactivated by small interfering RNA-mediated knockdown and by pharmacological inhibition with GSKJ4. The effects of targeted inactivation of JMJD3 were analysed in cultured fibroblasts and in the murine models of bleomycin-induced and topoisomerase-I (topoI)-induced fibrosis. H3K27me3 at the FRA2 promoter was analysed by ChIP.The expression of JMJD3, but not of UTX, was increased in fibroblasts in SSc skin and in experimental fibrosis in a transforming growth factor beta (TGF?)-dependent manner. Inactivation of JMJD3 reversed the activated fibroblast phenotype in SSc fibroblasts and prevented the activation of healthy dermal fibroblasts by TGF?. Pharmacological inhibition of JMJD3 ameliorated bleomycin-induced and topoI-induced fibrosis in well-tolerated doses. JMJD3 regulated fibroblast activation in a FRA2-dependent manner: Inactivation of JMJD3 reduced the expression of FRA2 by inducing accumulation of H3K27me3 at the FRA2 promoter. Moreover, the antifibrotic effects of JMJD3 inhibition were reduced on knockdown of FRA2.We present first evidence for a deregulation of JMJD3 in SSc. JMJD3 modulates fibroblast activation by regulating the levels of H3K27me3 at the promoter of FRA2. Targeted inhibition of JMJD3 limits the aberrant activation of SSc fibroblasts and exerts antifibrotic effects in two murine models.
EVALuna2:13457